2013
DOI: 10.9790/0853-0913539
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Effects of Oral Administration of Aqueous Extract of Hibiscus sabdariffa on Wistar Albino Rats

Abstract: Hibiscus sabdariffa had been reported to have a broad range of therapeutic effects. The effects of oral administration of Hibiscus sabdariffa aqueous extract on some biochemical parameters were studied in wistar albino rats. A total of twenty five (25) male albino rats were grouped randomly into groups. Group A (control), Group B (0.6g/100ml of water of HS extract) Group C (1.2g/100ml HS extract), Group D (1.8g/100ml HS extract) and Group E (1.8g/100ml + vitamin C) and treatment period was 28 days. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
3
2
Order By: Relevance
“…Therefore the significant increase in the serum chloride and bicarbonate ions following administration of aqueous extract of H. sabdariffa at various doses could be indicative of tubular and glomerular dysfunction. Our observation is contrary to the study by Emelike and Dapper [4].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore the significant increase in the serum chloride and bicarbonate ions following administration of aqueous extract of H. sabdariffa at various doses could be indicative of tubular and glomerular dysfunction. Our observation is contrary to the study by Emelike and Dapper [4].…”
Section: Discussioncontrasting
confidence: 99%
“…The serum potassium (K + ) level was decreased. This observation is in concert with studies by Abubakar et al [12] and Emelike and Dapper [4]. The mechanism for this is not clear.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Epidemiological studies have reported their wide range of remedies for metabolic syndromes including hypolipidemia, hypoazetomia, obesity, hypertension, diabetes, cancer, inflammation and the ability to regulate renal functions worldwide [1] [2] [3] [4] [5]. The therapeutic factors reported to be the attributing factors are the high content of vitamins and mineral elements as well as phytochemicals with antioxidants activities [6] [7].…”
Section: Introductionmentioning
confidence: 99%